Effect of eight weeks intermittent exercise training on oxidative stress indices in women with preterm labor after coronary artery bypass graft surgery (CABG): randomized clinical trial - Farnaz Sahhaf; Mehdi Nazari; Abbasali Dorosti (Mashhad University of Medical Sciences, 2020)
Introduction: Oxidative stress is one of the indicators that changes during preterm labor as well as cardiovascular diseases; several factors are effective on this index. Therefore, this study was performed with aim to evaluate eight weeks of intermittent exercise training on oxidative stress indices in women with preterm labor after coronary artery bypass graft surgery (CABG). Methods: This clinical randomized trial study was performed on 21 women with preterm delivery and a history of coronary artery graft surgery at Tabriz University of Medical Sciences in 2019. After random allocation, blood sample was taken from the samples and then the intervention group performed 24 sessions of intermittent exercise and the control group had her normal life. Serum levels of 8-hydroxy-2-dioxan-guanosine and urinary 8-hydroxy-2-deoxy-guanosine were measured before and after the intervention. Data were analyzed by SPSS software (version 19) and Shapirovilk, Independent t and t-student tests. P< 0.05 was considered statistically significant. Results: The exercise program in the intervention group caused a significant difference compared to pre-exercise in serum (P=0.003) and urinary (P=0.003) concentrations of 8-Hydroxy-2-dioxychuanosine. Intergroup difference of the variables such as weight (P=0.048), body mass index (P=0.004), fat percentage (P=0.002), and serum 8-hydroxy-2-dioxane guanosine (P=0.001) and urinary (P=0.001) were observed between the intervention and control groups. Conclusion: Intermittent exercise in women with a history of preterm labor undergoing coronary artery bypass graft surgery could cause changes in oxidative stress index.